2020
DOI: 10.1080/21655979.2020.1863015
|View full text |Cite
|
Sign up to set email alerts
|

Catalpol ameliorates psoriasis-like phenotypes via SIRT1 mediated suppression of NF-κB and MAPKs signaling pathways

Abstract: Psoriasis is a chronic inflammatory skin disease that affects approximately 2% of worldwide population, and causing long-term troubles to the patients. Therefore, it is urgent to develop safe and effective therapeutic drugs. Catalpol is a natural iridoid glucoside, that has several remarkable pharmacological effects, however, whether catalpol can alleviated psoriasis has not been explored. The goal of the present work is to study the role of catalpol in psoriasis in vivo and in vitro. Imiquimod-induced psorias… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 62 publications
2
35
0
Order By: Relevance
“…It has been documented that SIRT1 is involved in deacetylation of NF-κB and inhibition of NF-κB activation. 21 , 22 Next, we checked whether bergamottin could promote SIRT1 expression to inhibit NF-κB signaling. LPS stimulation decreased the mRNA level of SIRT1 in the lung tissues of mice ( Figure 5C ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been documented that SIRT1 is involved in deacetylation of NF-κB and inhibition of NF-κB activation. 21 , 22 Next, we checked whether bergamottin could promote SIRT1 expression to inhibit NF-κB signaling. LPS stimulation decreased the mRNA level of SIRT1 in the lung tissues of mice ( Figure 5C ).…”
Section: Resultsmentioning
confidence: 99%
“…SIRT1 is a protein deacetylase and has been shown to control p65 acetylation. 22 , 29 Most importantly, SIRT1 shows the capacity to alleviate LPS-induced inflammation. 30 , 31 Therefore, we speculated that bergamottin might regulate p65 activation through induction of SIRT1 and reduction of p65 acetylation.…”
Section: Discussionmentioning
confidence: 99%
“…The transfected HCC cells were seeded into 96-well plates (4 × 10 3 cells/well) and incubated for 0, 24, 48, and 72 h. Later, 10 µl of CCK8 reagent (Dojindo Laboratories) were added to incubate for another 2 h. At last, a microplate reader was used to measure the viability of cells [ 27 ].…”
Section: Methodsmentioning
confidence: 99%
“…SIRT1 deletion in endothelial cell (ECs), vascular smooth muscle cells (VSMCs), and monocytes/macrophages can increase OS, inflammation, foam cell formation, aging damage nitric oxide production, and autophagy and thus promote vascular aging and AS (Kitada et al, 2016). Liu et al found that catalpol inhibits NF-κB and MAPK signaling pathways by up-regulating the expression of SIRT1 mRNA and consequently reducing OS and TNF-α-induced inflammation response (Liu et al, 2021). Endogenous SIRT1 remarkably reduces endothelial activation without affecting the vasoconstriction and dilation function of ApoE−/− mice.…”
Section: Catalpol Reduces the Degree Of Inflammatory Response In Atherosclerosismentioning
confidence: 99%